Overcoming the Difficulties of Thermophilic Co-Digestion of Sewage Sludge and Beverage Industry Wastes in the Presence of Zeolite - Aleksandra Szaja; Agnieszka Montusiewicz; Magdalena Lebiocka (Energies)
The thermophilic anaerobic bioconversion of various wastes is still challenging, mainly due to process instability and economic profitability. This group includes orange wastes (OWs) and brewery spent grain (BSG), the main by-products generated by the beverage industry. In this study, a strategy allowing for improving methane production by the multicomponent co-digestion of sewage sludge (SS), OW, and BSG was proposed. To overcome the difficulties in the thermophilic co-digestion of those wastes, the application of natural zeolite (Z), i.e., clinoptilolite, was proposed. The experiment was performed in the batch mode at a temperature of 55 °C. Four experimental series were conducted with differing feedstock compositions, one of which was a control supplied only by SS. As compared with the control, in the series supplied by OW and OW with BSG, methane production decreased by 20% and 13%, respectively. In turn, significant improvements were achieved in the presence of Z. The most beneficial results were observed in the reactor supplied by SS, OW, and Z, characterized by a methane yield of 420.2 mLCH4/gVS, which is an increase of almost 14% as compared with the control. In this case, significantly improved stability parameters, as well as decreased presence of inhibitors, i.e., limonene and phenols, were achieved. It was also characterized by enhanced energy balance by 69%, as compared with the control.